First look and find : Baby Einstein (Chicago, Illinois Phoenix International Publications Inc, 2020)
"Look and find with your Baby Einstein friends. Search for hidden things in 7 playful scenes. Then turn to the end of the book for more challenges!" -- Back cover
Scientific Notions
Keywords: Counting Juvenile fiction; Picture puzzles; Shapes Juvenile fiction